A study on relationship between English proficiency and information literacy - Hamidreza Hoseini Dana; Hamidreza Karkehabadi; Elyas Elhami; Faeze Moeini (Management Science Letters, 2013)
This paper presents an empirical investigation to find the relationship between English proficiency and information literacy among some selected students from Islamic Azad University in city of Semnan, Iran. The proposed study uses regression analysis as well as Pearson correlation ratio to investigate the relationship between these two variables where information literacy is the dependent variable and English proficiency is an independent variable. The survey designed a questionnaire in four different categories and they were distributed among 364 participants out of 7200 people. Cronbach alpha has been calculated as 0.7125, which validates the overall survey. The result of our study indicates that there was a strong correlation between these two variables (r=0.88 Sig. = 0.01), which means as student get more familiar with English language they will have better general information.